Chemically Ordered Pt–Co–Cu/C as Excellent Electrochemical Catalyst for Oxygen Reduction Reaction. Issue 2 (21st January 2020) - Zhang, Libo; Ji, Xiangdong; Wang, Xiaoran; Fu, Yongqing; Zhu, Hong; Liu, Terence Xiaoteng
Abstract : This paper reveals the ordered structure and composition effect to electrochemical catalytic activity towards oxygen reduction reaction (ORR) of ternary metallic Pt–Co–Cu/C catalysts. Bimetallic Pt-Co alloy nanoparticles (NPs) represent an emerging class of electrocatalysts for ORR, but practical applications, e.g. in fuel cells, have been hindered by low catalytic performances owning to crystal phase and atomic composition. Cu is introduced into Pt-Co/C lattices to form PtCox Cu1−x /C (x = 0.25, 0.5 and 0.75) ternary-face-centered tetragonal (fct) ordered ternary metallic NPs. The chemically ordered Pt–Co–Cu/C catalysts exhibit excellent performance of 1.31 A mg −1 Pt in mass activity and 0.59 A cm −2 Pt in specific activity which are significantly higher than Pt-Co/C and commercial Johnson Matthey (JM) Pt/C catalysts, because of the ordered crystal phase and composition control modified the Pt-Pt atoms distance and the surface electronic properties. The presence of Cu improves the surface electronic structure, as well as enhances the stability of catalysts.